Peningkatan Hasil Belajar Peserta Didik Pada Pembelajaran IPAS Dengan Menggunakan Model Discovery Learning di Kelas IV SDN 15 Tabing Kecamatan Bonjol - Aisah, Fiza Nur; S, Farida (CV. PUSDIKRA MITRA JAYA, 2024)
This research is based on the low learning outcomes of students, this is because teachers have not used innovative learning models that can attract students' attention. The purpose of this study is to describe the improvement of social science learning outcomes by using the Discovery Learning model in Class IV SDN 15 Tabing, Bonjol District. This research is a classroom action research (PTK) that uses qualitative and quantitative approaches. It is carried out in two cycles, namely cycle I consists of 2 meetings and cycle II consists of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this study are teachers and students of grade IV of SDN 15 Tabing with a total of 30 students, 10 male students and 20 female students. Data collection techniques are in the form of observation, test, and non-test. The results of this study are guided by the recapitulation table of the results of the first cycle and the second cycle of research that have been presented in the discussion section, the results of this study show an increase in: a) the teaching module of the first cycle with an average of 81.81% qualification (good) and increased in the second cycle to 97.72% with qualification (very good), b) the implementation in the aspect of the teacher of the first cycle with an average of 82.8% qualification (good) and increased in the second cycle to 93.5% with qualifications (very good), in the aspect of students in the first cycle with an average of 82.8% of qualifications (good), and increased in the second cycle to 93.5% with qualifications (very good), c) the learning outcomes of students in the first cycle with an average of 76.78 with qualifications (adequate) and increased in the second cycle to 87.96 with qualifications (good). Based on these results, it can be concluded that using the Discovery Learning model can improve the learning outcomes of science and technology in students.